2013
DOI: 10.1017/jfm.2013.496
|View full text |Cite
|
Sign up to set email alerts
|

Threshold shear stress for the transition between tumbling and tank-treading of red blood cells in shear flow: dependence on the viscosity of the suspending medium

Abstract: Red blood cells are the subject of diverse studies. One branch is the observation and theoretical modelling of their behaviour in a shear flow. This work deals with the flow of single red cells suspended in solutions much more viscous than blood plasma. Below a critical shear rate (γ t ) the red cells rotate with little change of their resting shape. Above that value they become elongated and aligned in the shear field. We measuredγ t at viscosities (η 0 ) ranging from 10.7 to 104 mPa s via observation along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 38 publications
(55 reference statements)
7
34
0
Order By: Relevance
“…Although the inclination and phase angles seem to suggest a TB sequence interrupted by an SW, we cannot strongly say that intermittency occurs here due to buckling. This observation is consistent with the discussion in Fischer & Korzeniewski (2013) in reference to the work by Fedosov et al (2010). In contrast, we clearly see intermittency for the cells with the SSF state with a value of the bending stiffness that is within the experimental range and also close to those used by others in their simulations.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Although the inclination and phase angles seem to suggest a TB sequence interrupted by an SW, we cannot strongly say that intermittency occurs here due to buckling. This observation is consistent with the discussion in Fischer & Korzeniewski (2013) in reference to the work by Fedosov et al (2010). In contrast, we clearly see intermittency for the cells with the SSF state with a value of the bending stiffness that is within the experimental range and also close to those used by others in their simulations.…”
Section: Resultssupporting
confidence: 93%
“…For a comparison of the phase diagrams for the nearly spherical stress-free state and the discocyte stress-free state, we refer to our earlier work by Cordasco et al (2014), where we showed that the TB-TT transition occurs at lower Ca for the former case than the latter. There, we also presented a comparison of our phase diagram with experimental data by Abkarian et al (2007), Dupire et al (2012) and Fischer & Korzeniewski (2013). Peng et al (2014) as well as Tsubota et al (2013) also found that the TB-TT border shifts to lower Ca for the nearly spherical stress-free state.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Increasing the membrane viscosity may increase the effective viscosity ratio, leading to higher critical shear rate (see e.g. Fischer & Korzeniewski 2013). This parameter will also influence the detailed response of the cell.…”
Section: Responses In Shear Flowmentioning
confidence: 99%
“…Viscosity of the hemoglobin solution is about 5 times that of the plasma, leading to tumbling (TB) of RBCs. In vitro, TT motion of RBCs is observed when the suspending fluid has a high enough viscosity η 0 [43]. Furthermore, confinement favors TT [52] even with lower η 0 .…”
mentioning
confidence: 99%